Kajian Tingkat Kerentanan dan Ketahanan Masyarakat di Kawasan Permukiman Pesisir Kota Pariaman Terhadap Bencana - Mahda Huriyatul Syaputri Syam; Ragil Haryanto (Jurusan Perencanaan Wilayah dan Kota, 2022)
Pariaman City is one of the cities in the western part of Sumatra Island which is prone to disasters because there are two tectonic plates meeting, namely the Indo-Australian and Eurasian at the bottom of the Indian Ocean. So that in the event of a disaster the area most at risk of being affected is the coastal residential area of Pariaman City which includes fourteen villages. This study aims to assess the level of vulnerability and resilience of coastal communities in Pariaman City to disasters. The method used in determining the level of vulnerability is the overlay method on indicators of physical, social and economic vulnerability. The results of study showed a high level of vulnerability to disasters includes Karan Aur, Pasir, Lohong and Naras 1, the medium vulnerability level includes Marunggi, Ampalu, Manggung, Pasir Sunur, Naras Hilir, and Taluk, and the low vulnerability level includes Pauh Barat Village, Balai Naras, Apar, Padang Birik-Birik). The method used in determining community resilience is CCR (Coastal Community Resilience). The results showed that three of the eight elements of resilience is below standard, such us society and economic (Manggung), land use and structural design (Lohong, Manggung, and Balai Naras), warning and evacuation (Kelurahan Pasir , West Pauh Village, Amaplu Village and Marunggi Village). It can be concluded that the coastal communities of Pariaman City have a high tendency of vulnerability to disasters but also have a high tendency of resilience in dealing with these disasters. So to reduce the risk, it is necessary to regulate land use and recommendations to increase the element of resilience according to standards.